A Vision of Hell in Ancrene Wisse and Sawless Warde - Ana María Hornero Corisco (Miscelánea: A Journal of English and American Studies)
The aim of this paper is to bring attention to an aspect shared by two of the works which constitute the Katherine group: both try to persuade the reader to choose the right path leading to salvation by presenting, each one in its own style, a moving and convincing picture of hell. Imagery, alliteration and witty devices are at its best in these descriptions, making of these passages the most vivid throughout the pages of Ancrene Wisse and Sawles Warde.